MENDESKRIPSIKAN KEHIDUPAN TOLERANSI BERAGAMA DESA SIKAKAP MELALUI PROJEK PENGUATAN PROFIL PELAJAR PANCASILA - Umam, Muhamad Safiul (Universitas Pendidikan Ganesha, 2023)
The residents of Sikakap Village adhere to three major religions, namely, Christianity, Islam and Catholicism (Sikakap in the data). This research aims to